The Impact of Corporate Governance Mechanisms on the Quality of Financial Reporting Information: A Field Study on Some Banks and Companies in the Red Sea and Kasala States, Sudan - Hussein, Waleed Hussein Hassan (Journal of Economic, Administrative and Legal Sciences, 2025)
The study mainly aimed to know the impact of applying corporate governance mechanisms on achieving the quality of companies’ financial reporting information, in addition to highlighting the importance of financial reporting information quality, and benefiting from corporate governance mechanisms in achieving it. To achieve the objectives of the field study, the inductive approach, the historical approach, and the descriptive analytical approach were adopted. The researcher distributed (150) questionnaire forms to a sample of employees in the study community, which was represented by some Sudanese banks and companies in the Red Sea and Kasala states. All questionnaire forms were 100% returned. After analyzing the data, the study found several results that proved the validity of the hypotheses, including that achieving the independence of the board of directors contributes to achieving the quality of financial reporting information, and that applying corporate governance mechanisms contributes to achieving the quality of information related to the company's resources. The study concluded with a number of recommendations, the most important of which is to work on spreading the culture of applying corporate governance among companies in the Sudanese business environment and issuing the necessary legislation to apply corporate governance in the Sudanese business environment to achieve the quality of companies’ financial reporting information.
Keywords: Corporate governance mechanisms; information quality; companies’ financial reporting